The effect of educational intervention based on the PRECEDE-PROCEED model on self-care behaviors and quality of life of hypertensive patients - Rakhshani, Tayebeh; Tahmasebi, Zahra; Ghahremani, Leila; Kamyab, Amirhossein; Khani Jeihooni, Ali (Frontiers in Public Health, 2024)
Background To prevent the harmful consequences of hypertension and enhance the quality of life of hypertensive patients, the use of educational models is highly suggested. Therefore, the present study was designed to determine the effect of education based on the PRECEDE-PROCEED on self-care behaviors and the quality of life of hypertensive patients in Kazeroon city, Iran, in 2023. Methods A total of 120 hypertensive individuals who were referred to Kazeroon city health centers participated in the current quasi-experimental study. The participants were divided into two experimental and control groups using a random sampling technique (60 participants in each group). The self-care behaviors questionnaire, the quality of life questionnaire, and a questionnaire based on the PRECEDE-PROCEED model were used as the data acquisition techniques. Both groups completed the questionnaires before and 2 months after the intervention. The educational program included a six-session, 50–60 min training program using three different teaching methods (speaking, Q&A, group discussion, and peer training) in health facilities. The data were examined using paired t, independent t, and chi-square statistical tests after being entered into the SPSS 24 statistical program. Results Following the intervention, the experimental group showed significantly higher values in quality of life, knowledge, attitude, enabling and reinforcing factors, and self-care behaviors compared to the control group (p < 0.001 for all comparisons). The experimental group also exhibited a significant reduction in systolic blood pressure measures compared to the control group (p < 0.001). Conclusion In the present study, education based on the PRECEDE-PROCEED model and focusing on blood pressure self-care behavior in patients with hypertension led to a decrease in their systolic blood pressure measures and improved their quality of life.